Phylogenetic Tree 16S rRNA Gene of Acinetobacter soli Isolated from the Prepuce of Aceh Cattle - Admi, Masda; Darmawi, Darmawi; Ferasyi, Teuku Reza; Dasrul, Dasrul (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: In the pre-seed area of healthy Aceh cattle, it is possible to be contaminated with pathogenic bacteria that can interfere with the reproductive system. This study is needed to identify these pathogenic bacteria using a molecular approach, in an effort to prevent infection. AIM: The aim of the present study was to construct phylogenetic tree relationships of Acinetobacter soli identified in the preputial area of Aceh cattle by molecular analysis using 16S rRNA gene sequencing. MATERIALS AND METHODS: A total of 75 preputial specimens were obtained from Indrapuri’s Breeding and Forages Center of Aceh Cattles, Indrapuri district, Banda Aceh, Indonesia. The samples were processed for culture using standard conventional methods. The extraction of genomic DNA and the amplification of the 16S rRNA gene were assayed using polymerase chain reaction. A phylogenetic tree was constructed using distance matrices using the neighbor-joining model of the molecular evolutionary genetic analysis software 6.1 software. RESULTS: The results showed that of 75 preputial swab samples, 18 (24%) were positive for A. soli isolates. There was a 100% sequence similarity to A. soli prototype strain B1 and a 99% similarity to Acinetobacter parvus prototype strain LUH4616, Acinetobacter baylyi strain B2, A. venetianus strain ATCC 31012, as well as a 99% similarity to Acinetobacter baumannii strain DSM 30007, the strain ATCC 19606, and the strain JCM 6841, respectively. We concluded that A. soli-positive presentation in the preparation of Aceh cattle has 100% sequence similarity of 16S rRNA with A. soli strain B1. CONCLUSIONS: The conclusion of this study is that, based on the construction of a phylogenetic tree, it shows that 24% of the bacterial isolate is related to A. soli. It is essential to conduct a regular survey for bacterial contamination and to increase worker awareness and education about hygiene standards.